DISTRIBUSI DAN DAERAH JELAJAH LUTUNG (Trachypithecus auratus sondaicus) DI TAMAN WISATA ALAM PANGANDARAN - Teguh Husodo; Erri Noviar Megantara (Universitas Padjadjaran, 2002)
ABSTRACTThe study distribution and population of lutung(Trachypithecus auratus sondaicus) in Pangandaran NaturalRecreational Park (TWAP) was conducted in January 2001through census method. Broad inventory observation wasapplied to identified plant community and dominant plantspecies. There are 12 lutung groups and evenly distributed in 37,7 ha area of TWAP, thus the density of lutung is rangebetween 35-36 groups/km2. Population average on groups as13,1-13,5, 20-21 are maximized and 5-6 are minimizingpopulation. Composition of sex ratio average on eachgroup was 1,9 adult male/group, 6,9-7,5 adult female/group, 2 subadult/group, 2,7-3,2 young/group and1 infant/group. Lutung habitat on TWAP were secondaryforest, with dominance vegetation are laban (Vitexpubescens), kisegel (Dillenia exelsa) and marong(Cratoxylum formosum), nyamplung (Callophylluminophylum), ketapang (Terminalia catappa), waru (Hibiiscustiliaceus) and butun (Barringtonia asiatica). Recorded 40 of 60species have 1 % frequency index were lutung food. Duringthe studies members splitter recorded from their group, like A, B and C groups to A1-1, A1-2, B1, B2, C2-1 and C2-2. Average of territory area of all groups were 2,78 ha, 6,67ha are maximized and 2,78 ha are minimized.Keyword :Lutung, distribution, homerange, population, PananjungPangandaran Nature Reserve.